2013
DOI: 10.1002/jnr.23287
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intercostal muscle pathology in canine degenerative myelopathy: A disease model for amyotrophic lateral sclerosis

Abstract: Dogs homozygous for missense mutations in the SOD1 gene develop a late-onset neuromuscular disorder called degenerative myelopathy (DM) that has many similarities to amyotrophic lateral sclerosis (ALS). Both disorders are characterized by widespread progressive declines in motor functions accompanied by atrophic changes in the descending spinal cord tracts , and some forms of ALS are also associated with SOD1 mutations. In end-stage ALS, death usually occurs as a result of respiratory failure due to severe fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…A presumptive clinical diagnosis is made by ruling out potential causes of compressive myelopathy; however, confirmation requires histopathological examination of the spinal cord (16). The pathological features of DM are similar to the pathological features of ALS (17)(18)(19)(20)(21)(22). DM has been confirmed in over 24 breeds (16,23) and presumptively reported in another nine breeds (16).…”
Section: Significancementioning
confidence: 99%
“…A presumptive clinical diagnosis is made by ruling out potential causes of compressive myelopathy; however, confirmation requires histopathological examination of the spinal cord (16). The pathological features of DM are similar to the pathological features of ALS (17)(18)(19)(20)(21)(22). DM has been confirmed in over 24 breeds (16,23) and presumptively reported in another nine breeds (16).…”
Section: Significancementioning
confidence: 99%
“…Clinical signs appear in pelvic limbs as spastic upper motor neuron (UMN) paresis and general proprioceptive ataxia, which progresses to flaccid tetraplegia and dysphagia if euthanasia is delayed (Coates and Wininger, ). As with some forms of familial amyotrophic lateral sclerosis (ALS), DM is associated with mutations in superoxide dismutase 1 ( SOD1 ; Andersen et al, ; Coates and Wininger, ; Morgan et al, ). DM occurs in many breeds and is typically accompanied by the SOD1 missense mutation SOD1:c.118G→A , which predicts a p.E40K substitution (Awano et al, ).…”
mentioning
confidence: 99%
“…Results reported in the literature vary significantly according to muscle group and breed. There is another important discrepancy; some authors reported significant MN loss , while others reported no MN loss in the same breed and spinal segments (Morgan et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…It is difficult to explain the reasons for this discrepancy using the available data, but ALS actually encompasses a spectrum of disorders, and it is possible that fiber type grouping occurs in some forms of the disease and not in others (Soraru et al, 2008). Since no fiber type grouping in intercostal muscles (Morgan et al, 2013) or in pelvic limb muscles (Shelton et al, 2012) has been identified in PWCs with late-stage CDM, it can be assumed that this breed replicates muscle pathology of only some forms of ALS muscle (Morgan et al, 2013). A markedly increased ratio of type 1 to type 2 fibers seen in end-stage PWCs, relative to that in a normal PWC, has also been reported in hind limb muscles from an ALS mouse model with a low copy number of a mutant SOD1 transgene (Acevedo-Arozena et al, 2011).…”
Section: Muscle Atrophymentioning
confidence: 91%
See 1 more Smart Citation